Analysis of Exclusive Breastfeeding Program in Nusa Indah Public Health Center and Lingkar Barat Public Health Center Bengkulu Year 2019 - Bintang Pratiwi Pratiwi; Riska Yanuarti; Henni Febriawati; Wulan Angraini; Muhammad Arif Tobing (Amerta Nutrition, 2020)
Background: The highest coverage of exclusive breastfeeding data from Bengkulu City Health Office was Nusa Indah Public Health Center (86.9%) and the lowest was Lingkar Barat Public Health Center (63.8%).Objective: The research objective is to determine the implementation of exclusive breastfeeding programs seen from the input, process, output in the city of Bengkulu in 2018.Methods: This was an observational analytic study with a qualitative approach. The informants consisted of nutrition workers, midwives, health promotor, heads of Public helath center and mothers who participated in the exclusive breastfeeding program at the puskesmas. This research was carried out in both Bengkulu City Health Center, starting from July to August 2019. Data analysis was done by data reduction, data presentation and conclusion drawing and verification.Results: The study showed that the executors of the exclusive ASI program consisted of nutrition workers, midwives and promkes, using BOK funds, material on exclusive breastfeeding, tools in the form of infant pantom, breast pantom, breast milk, with counseling, counseling and IMD methods. The implementation process is Exclusive ASI socialization, formation and guidance of ASI Suport group. Implementation with counseling, and counseling. Control by looking at data obtained from posyandu.Conclusion: The Nusa Indah Puskesmas has been successful because the ASI support group has played an active role in assisting the implementation of the Exclusive ASI program, while the West Lingkar Puskesmas was not successful because the officers did indeed obtain real data in the field.